The Role of Diniyah Madrasah in Forming National Character - Besari, Anam (STAI MA'ARIF MAGETAN, INDONESIA, 2023)
Madrasah Diniyah is an educational institution that is quite old and has developed along with the development of education in Indonesia, so that its existence cannot be separated from the country which has the largest Muslim population in the world. Examined in terms of language, Madrasah comes from Arabic, this shows its uniqueness, because Madrasah Diniyah is known as the oldest Islamic education institution. The journey of Madrasah Diniyah from time to time experiences change after change by adapting to the development of education in this beloved country. Little by little, these changes are to achieve perfection in the system and model that is developing, which in the end Madrasah Diniyah still exists in the midst of society and its existence is still very much needed by society itself. Madrasah Diniyah's presence in today's society has a big influence in shaping the character of the nation's children, where the identity of this nation is starting to be eroded. Madrasah Diniyah is able to ward off and maintain the identity of this nation, so it is not excessive for the presence of the Government to provide equality between Madrasah Diniyah and Formal Education in this country. This will strengthen the existence of Madrasah Diniyah which the community considers capable of responding to the challenges faced by the Indonesian nation today and in the future.